Effects of Metformin and diet on hemoglobin, cholesterol and triglyceride levels of Type 2 diabetic Patients - Talib Almuswie, Rana; Z. Al-Rumaidh, Shaymaa; R. Lafta, Luma; A.Hafedh, Alyaa (University of Thi-Qar Journal of Science, 2017)
Metformin is recommend as the first line oral agent to be used patients with non-insulin-dependent diabetes mellitus(Type 2 Diabetic).The study was prospectively performed in diabetic and endocrine center of Nassiriyah city .The present study aimed to shed light on metformin and hemoglobin(Hb) and lipid profile in type II diabetic patients with diet and without diet . Our study included 60 patients treated with metformin for Twelve-week . The subjects were divided into three groups. Group I as control, group II patients received Metformin- (1000/2 mg/day) with diet and group III patients received the Metformin-(1000/2 mg/day) without diet all these patient had been selected from those patients visit . The Hb concentration and lipid profile were been examine after 3 months of treatment.In present study we found the hemoglobin concentration reduced in group II with diet patient compare with the group III and control group also reduced in the group III without diet patient compare with control group, as same time This study showed that the treatment with metformine led to, reductions observed in the cholesterol concentrations of the group II diabetic patients with diet compared with the group III administered MET respective without diet diabetic and compared with control, Also we found the triglyceride concentrations of diabetic patients in group administered MET respective with diet were significantly (p<0.05) reduced compared with that of without diet diabetic and control therefore it was considered predisposing factor to reduced damage diabetes. For this reason; continuous taking of metaformin should be important.